2021
DOI: 10.1021/acsomega.0c05809
|View full text |Cite
|
Sign up to set email alerts
|

Solar Light-Irradiated Photocatalytic Degradation of Model Dyes and Industrial Dyes by a Magnetic CoFe2O4–gC3N4 S-Scheme Heterojunction Photocatalyst

Abstract: Magnetic CoFe2O4–gC3N4 nanocomposites were successfully synthesized, and their photocatalytic activities toward the decomposition of model synthetic dyes (e.g., methylene blue, methyl orange, and Congo red) in the presence of H2O2 were evaluated under simulated solar light irradiation. The 50CoFe2O4–50gC3N4 nanocomposite exhibited the highest catalytic activity. The catalytic activity of 50CoFe2O4–50gC3N4 toward the photodegradation of some industrially used dyes (such as Drimaren Turquoise CL-B p, Drimaren Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 87 publications
0
47
0
Order By: Relevance
“…22-1086]. 30 , 31 The presence of only peaks corresponding to pure CF hs indicated the formation of single-phase CF hs by the employed hydrothermal synthetic route. The XRD patterns of GO ( Figure S2 ) and GO sp were identical to each other, which confirmed that no intrinsic structural changes occurred due to the formation of the spongelike nature.…”
Section: Resultsmentioning
confidence: 99%
“…22-1086]. 30 , 31 The presence of only peaks corresponding to pure CF hs indicated the formation of single-phase CF hs by the employed hydrothermal synthetic route. The XRD patterns of GO ( Figure S2 ) and GO sp were identical to each other, which confirmed that no intrinsic structural changes occurred due to the formation of the spongelike nature.…”
Section: Resultsmentioning
confidence: 99%
“…S‐scheme photocatalysts demonstrate efficient performances for reactive oxygen species (ROS) evolution in pollutant decomposition and sterilization processes, e.g., CoFe 2 O 4 /g‐C 3 N 4 , 0D/2D CeO 2 /g‐C 3 N 4 , S‐pCN/WO 2.72 , Sb 2 WO 6 /g‐C 3 N 4 , OVs‐Bi 2 O 3 /Bi 2 SiO 5 , In 2 O 3– x (OH) y /Bi 2 MoO 6 , and BP/BiOBr, Bi 2 MoO 6 /CdS, BiOCl/CuBi 2 O 4 , Bi 2 WO 6 /g‐C 3 N 4 , SnNb 2 O 6 /Ag 3 VO 4 , BiOBr/BiOAC 1–– x Br x , BiOI/Bi 2 WO 6 , Bi 2 O 3 /TiO 2 , In 2 S 3 /Bi 2 O 2 CO 3 , ZnO–V 2 O 5 –WO 3 , S‐doped g‐C 3 N 4 /TiO 2 , BiVO 4 /Ag 3 VO 4 , CdS/UiO‐66, α‐Fe 2 O 3 /Bi 2 WO 6 , Cd 0.5 Zn 0.5 S/g‐C 3 N 4 , Sb 2 WO 6 /BiOBr, and Bi 2 MoO 6 /g‐C 3 N 4 /Au. [ 28,76–97 ] Li et al utilized thin black phosphorus (BP) to couple BiOBr nanosheets to construct S‐scheme BP/BiOBr nanoheterojunction for H 2 O 2 evolution, [ 80 ] as shown in Figure a. H 2 O 2 evolution rate over 10BP/BiOBr is 2.6 times than that over BiOBr.…”
Section: S‐scheme Photocatalystsmentioning
confidence: 99%
“…[ 8 ] Also, the narrow band gap energy value of MFO:SCNNS (1:1) nanocomposite (E g = 2.32 eV) allowed it to efficiently absorb solar radiation. [ 123 ] Hence, due to increased light absorption in solar spectrum range, the designed heterojunction served as an effective visible light responsive photocatalytic material. Moreover, under refluxing condition, the degradation efficiency was also noted to be quite satisfactory because of the enhanced e − /h + pair separation and movement rate at higher temperature.…”
Section: Resultsmentioning
confidence: 99%